Induced resistance to the greenbug aphid Schizaphis graminum Rond. in species of the genus Triticum - S. D. Rumyantsev; S. V. Veselova; G. F. Burkhanova; I. V. Maksimov (Вавиловский журнал генетики и селекции)
The greenbug aphid Schizaphis graminum Rond. causes a significant loss of the grain harvest. Therefore, to improve plant resistance to aphids is one of the topical tasks. The problem of creating varieties resistant to phloem-feeding insects is quite urgent, since the mechanisms procuring the resistance of plants to insects are not fully understood. Nevertheless, modern literature describes some mechanisms associated with changes in the redox state of colonized plants. Besides, attention is being increasingly focused on the study of mechanisms that underlie inducible resistance to aphids in wheat and are regulated by hormonal signaling systems. To detect connections among the redox status, indicators of resistance (antibiosis and endurance) of wheat plants to the pest, and induction of the jasmonate (JA) and salicylate (SA) signaling pathways, we studied accessions of three species of wheat plants – Triticum aestivum L., T. monococcum., and T. timopheevii Zhuk.– infested with S. graminum greenbugs by physiological, biochemical, and molecular methods. Analysis of antibiosis and endurance showed that T. timopheevii k-58666 and T. monococcum k-39471 were resistant to S. graminum, the latter accession being the most enduring. High hydrogen peroxide contents and high peroxidase activities were detected in the resistant plants. We investigated the expression of genes encoding PR proteins, including markers and regulators of the salicylate (TaRboh, TaPAL, Tapr1, TaPrx) and jasmonate (TaPI, TaLOX, TaPrx) signaling pathways. At the early stage of infestation in the susceptible T. aestivum variety Salavat Yulaev, the expression of only jasmonate-dependent genes was activated in response to plant damage. In the resistant T. timopheevii accession k-58666, expression of only salicylate-dependent genes was activated, while the aphid reproduction was practically absent. In the resistant T. monococcum accession k-39471, expression was activated in both the salicylate-dependent and jasmonate-dependent gene groups. We assume that the oxidative burst in the resistant forms of wheat was induced via the activation of the SA signaling pathway, which was of crucial importance in the further cascade of chemical reactions leading to the development of resistance.